THE EFFECT OF BIOLOGICAL AND ANORGANIC FERTILIZERS ON Azotobacter POPULATION OF PAKCOY CULTURE NUTRIENT FILM TECHNIQUE - Ansirih Ansirih (Universitas PGRI Palembang, 2020)
Hydroponics as NFT (Nutrient Film Technique) system is one of the mechanism planting with additional water until 3 mm from roots. In hydroponic system, the anorganic biofertilizer that contained in the media is a major nutrition for plant. Hydroponic system depends on anorganic material as nutrients supply. The use of biofertilizer was expected to reduce the dosage of anorganic fertilizer that applied in hydroponic system. The aims of the research were to find the best combination dosageof biofertilizer and anorganic biofertilizer on the population of Azotobacter, and yield of pakcoy (Brassica rapa L.). The experiment used randomized block design (RBD) which consisted of four combination that is anorganic fertilizer (100%, 75%, and 50%) + 100% biofertilizer 150 mL. The result showed that the combination of 100% biofertilizer and 50% anorganic fertilizer can reduce the use of anorganic fertilizer up to 50%, and can increase the population of Azotobacter, and yield of pakcoy (Brassica rapa L.).